2016
DOI: 10.1590/1809-4392201500072
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols isolated from endophytic fungus Colletotrichum gloeosporioides(Melanconiaceae)

Abstract: Endophytic fungi are fungi that colonize internal tissues of plants. There are few studies of compounds isolated from endophytic fungi of Amazon plants. Thus, the aim this study was the isolation and structural identification of sitosterol (1), stigmasterol (2), sitostenone (3), squalene (4), ergosterol (5) and ergosterol peroxide (6) from fungus Colletotrichum gloeosporioides isolated as endophytic from Virola michelli, a typical Amazon plant, used in folk medicine against skin infection. Compounds were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
1
6
0
2
Order By: Relevance
“…Colletotrichum spp. was found to be the source of "phytosterols" [26]. Thus, the analysis confirms marine fungi are potential due to their adaptation in salt-rich environment.…”
Section: Analysis Of Mycoflorasupporting
confidence: 55%
“…Colletotrichum spp. was found to be the source of "phytosterols" [26]. Thus, the analysis confirms marine fungi are potential due to their adaptation in salt-rich environment.…”
Section: Analysis Of Mycoflorasupporting
confidence: 55%
“…: fusarentine 6,7-dimethyl ether, monocerin, and colletotrialide (Tianpanich et al, 2011), stigmasterol, sitostenone, squalene, ergosterol and ergosterol peroxide (Carvalho et al, 2016) were identified. Colletotrichum species have been identified to produce a variety of secondary metabolites genes, including flavones, peptides and terpenes (Crouch et al, 2014) and many other metabolites as Jayawardena et al (2016) shows.…”
Section: Discussionmentioning
confidence: 99%
“…16 The sterols ergosterol (5), ergosterol peroxide (6), cerivisterol (7), sitosterol (8), and stigmasterol (9) were isolated by chromatographic procedures and identified by NMR and with literature data. [17][18][19] Analysis of the control extracts by MS showed the absence of the isolated compounds in the culture medium, confirming that the isolated compounds are secondary metabolites produced by the fungus Aspergillus FRIZ12 and not from the culture medium.…”
Section: Isolated Compoundsmentioning
confidence: 76%